Buckling of an externally pressurised toroidal shell of revolution with a doubly-symmetric parabolic-ogival cross-section. (June 2020) - Enoma, Nosakhare; Zingoni, Alphose
Abstract: As part of recent work on the structural behaviour of toroidal shells, this paper presents results of a numerical study on the buckling resistance of a closed toroidal vessel with a doubly-symmetric parabolic-ogival cross-section, subjected to uniform external pressure. The analysis was carried out on both geometrically perfect and imperfect elastic steel shells, and boundary conditions resulting in the lowest buckling pressure were adopted. A range of shell geometries and possible imperfections of the geometry were considered. The study shows that buckling initiates as non-axisymmetric deformations in the weakest zones near the top and bottom edges of the outer segment of the vessel. The buckling strength of the vessel is found to be strongly dependent on the geometrical parameters of the cross-section, and parameters giving the largest buckling resistance of the vessel are identified. While the buckling behaviour is sensitive to initial geometric imperfections in the form of eigenmodes, the vessel is generally stable after bifurcation.